2008
DOI: 10.1016/j.jmb.2008.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Transition-State Entropy for Aggregation Suggests How the Growth of Sickle Cell Hemoglobin Polymers can be Slowed

Abstract: Sickle cell anemia is associated with the mutant hemoglobin HbS, which forms polymers in red blood cells of patients. The growth rate of the polymers is several micrometers per second, ensuring that a polymer fiber reaches the walls of an erythrocyte (which has a 7-μm diameter) within a few seconds after its nucleation. To understand the factors that determine this unusually fast rate, we analyze data on the growth rate of the polymer fibers. We show that the fiber growth follows a first-order Kramerstype kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…The simulations clearly demonstrate that the growth of HbS fibers is due to the attachment of HbS monomers, rather than by association of precursor aggregates performed in the growth medium. This result is consistent with analyses of experimental data on the growth of HbS polymer fibers (11,12,45). In addition, we find that the active sites on the HbS fiber surface are not always in the same layer in the direction perpendicular to the fiber axis, so individual strands may vary in length.…”
Section: Formation Dynamics Of Hbs Polymer Fibersupporting
confidence: 90%
See 1 more Smart Citation
“…The simulations clearly demonstrate that the growth of HbS fibers is due to the attachment of HbS monomers, rather than by association of precursor aggregates performed in the growth medium. This result is consistent with analyses of experimental data on the growth of HbS polymer fibers (11,12,45). In addition, we find that the active sites on the HbS fiber surface are not always in the same layer in the direction perpendicular to the fiber axis, so individual strands may vary in length.…”
Section: Formation Dynamics Of Hbs Polymer Fibersupporting
confidence: 90%
“…The presence of the nucleation barrier makes nucleation events rare. Once a nucleus forms, HbS fibers grow quickly, likely by the addition of HbS monomers (8,(10)(11)(12)(13). The chirality of HbS molecules, which lack internal planes of symmetry, results in a particular structure of the HbS fiber, comprised of seven double strands in the style of a twisted rope (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The good correspondence of the J(T), q(T), and R(T) dependencies to the exponential function ( Fig. 4) (32,42,43) justifies such extrapolations. The comparison reveals that the addition of heme enhances J by more than two orders of magnitude and R by a factor of~10 and shortens q by approximately two orders of magnitude.…”
Section: Kinetics Of Nucleation and Growth Of Hbs Polymer Fibers In Tmentioning
confidence: 71%
“…To understand the acceleration of the growth rate in the presence of heme, we note that Vekilov et al (43) showed that the hydration shell around the HbS molecules largely determines their rate of attachment to the growing polymer fiber. The action of heme on the growth rate likely occurs through modification of this shell, discussed above and in Pan et al (48).…”
Section: Discussionmentioning
confidence: 99%
“…Diffusive dynamics play an important role in many biological transport processes, including intracellular transport [1][2][3], bacterial motility [4], biofilm growth [5], and protein aggregation, complexation, and crystallization [6][7][8], and additionally may affect the efficacy of emerging nanomedicine-based therapies [9][10][11][12]. Understanding the role of dynamics in both natural and engineered processes requires methods to quantify the motion of microand nanoscale particles in complex biological media.…”
Section: Introductionmentioning
confidence: 99%